Źródła referencyjne i rekonstrukcyjne do geowizualizacji porównawczej grodu w Gieczu w XII i XXI wieku - Zawadzki, Jakub (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2023)
This article presents the process of presenting and valorizing spatial, historical and archaeological data for creating a comparative geovisualisation of the Giecz stronghold in two time frames: the 12th and 21st centuries. The aim of this work is related to the concept of protecting and sharing cultural heritage. Special attention has been paid to the presentation of spatial archaeological and historical data in a 3D virtual environment, with a possibility of presenting them in a Virtual Reality (VR) environment. From a cartographic point of view, special emphasis was placed on the proper integration of cartographic, remote sensing and graphic sources in a geomatic process for implementing the model into interactive virtual environments.